A Longitudinal Examination of the Association Between Meaning in Life, Resilience, and Mental Well-Being in Times of Coronavirus Pandemic - Arslan, Gökmen; Yıldırım, Murat (Frontiers in Psychology, 2021)
The coronavirus disease possesses an important threat to people’s health and wellbeing. The purpose of the present study is to longitudinally examine whether meaning in life before the pandemic increases resilience and mental wellbeing during the coronavirus pandemic. The sample of the study comprised of 172 young adults (72% women) in a public university in an urban city of Turkey. Participants ranged in age between 18 and 40 years (M= 20.87, SD= 3.92). Mediation analyses were performed to examine the impacts of meaning in life on the outcomes across the two waves of data. Findings from these analyses revealed that meaning in life before the pandemic had a significant predictive effect on resilience and mental wellbeing of young adults during the coronavirus disease. Resilience also mediated the impacts of meaning in life on mental wellbeing indicators at the second time. These results suggest the importance of meaning-based preventions and interventions designed to build up resilience experiences for improving psychological health and wellbeing during a public health crisis.